Buller men and batty bwoys : hidden men in Toronto and Halifax black communities - Crichlow, Wesley E. A. (Wesley Eddison Aylesworth), 1961- (Canadian electronic library. Books collection., 2004)
Buller Men and Batty Bwoys offers the reader critical insight into the complex lives of Black gay and bisexual men in Canada. Equally important, Crichlow's research makes a substantial and original contribution to the limited body of academic work in this area.